Evaluation of the process of implementing a professional nurse education program - ., Ennimay; Budi Santoso, Maruf Akbar, (Opción, 2020)
The objective of this research was to evaluate the process of implementing a Professional Nurse Education Program at Institutes of Health Sciences in Pekanbaru, Indonesia. This research was a qualitative approach using CIPP (Context, Input, Process, and Product) evaluation model with content analysis. As a result, there were two themes, the first theme showed that the preceptorship method was used in clinical process of nursing practice. In Conclusion, the preceptors who meet the criteria and discipline are very important in the process of providing practical guidance to nursing profession students in Indonesia to make a good experience for the students